Applications of KIST-USANS Instrument at HANARO Cold Neutron Facility to Hard Matter - Kim, Man Ho (대한금속재료학회 추계학술대회, 2022)
Often micron-sized precipitates are observed in hard matters like alloys, of which the quantity and shape affect the mechanical properties. Some powders are used in catalysts, and composites, of which performance partly depends on the shape of the powders. Cracks or voids can negatively affect material performance. Micro-structures in magnetic material may exist, but are not easy to characterize it due to the interference from magnetic scattering and a limitation of available neutron measurement technique. Quantitative characterization of those materials, without particular sample preparation that can change the structure or morphology, is important to correlate the structure and properties. Since neutrons have strong penetration capabilities to those opaque hard materials, the structure of thick and large samples (1mm thick x 20 mm length) can be measured, which provides the reliable averaged-structure information. The high Q-resolution USANS instrument can measure from sub-micron in